Successful medical management of uterine arteriovenous malformation - Rastogi, Aparajita; Kumari, Neetu; Rajbhar, Sarita; Thakur, Pushpawati; Majumdar, Sagarika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Uterine Arteriovenous malformation (AVM) is defined as abnormal communication between the uterine arteries and veins. This can be congenital or acquired. It occurs more frequently in reproductive age group women. Patient present with complain of spotting per vagina to catastrophic bleeding per vaginum. Diagnosis is based upon clinical history and findings in colour doppler of pelvis. The treatment depends upon the age of the patient, her symptoms, age, desire of future fertility and localization and size of the lesion. Uterine artery embolization is the most commonly used treatment for symptomatic uterine arteriovenous malformation. There were few case reports of successful medical management of uterine AVM with GnRH agonist. But GnRH agonist have side effects that restrict its long time use and for Uterine artery embolization, clinical skill and set up is required and it is not available at every hospital. Here is presenting a case report of successful medical management of uterine arteriovenous malformation with combined oral contraceptive pills (coc). COC are easily available everywhere and its side effects are few if compared with GnRH agonist.